2017
DOI: 10.3390/ijms18122753
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuretin Attenuates MPP+-Induced Neurotoxicity through Akt/GSK3β and ERK Signaling Pathways

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease. It is caused by the death of dopaminergic neurons in the substantia nigra pars compacta. Oxidative stress and mitochondrial dysfunction contribute to the loss of dopaminergic neurons in PD. Sulfuretin is a potent antioxidant that is reported to be beneficial in the treatment of neurodegenerative diseases. In this study, we examined the protective effect of sulfuretin against 1-methyl-4-phenyl pyridinium (MPP+)-induced cell model of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 78 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…With respect to apoptosis of dopaminergic cells in PD [27,52,53], ERK, and P38 activators such as sulfuretin and chrysotoxine have shown efficacy in in vitro models of PD, by blocking apoptosis. Pariyar et al showed that sulfuretin protects neuronal cells against MPP + -induced damage through the activation of ERK and its downstream anti-apoptosis effector, Bcl-2, in SH-SY5Y cells [54]; however, sulfuretin has not been studied in an in vivo PD model. In addition, sulfuretin protected dopaminergic neurons from amyloid beta neurotoxicity in an in vitro model of Alzheimer’s disease [55].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to apoptosis of dopaminergic cells in PD [27,52,53], ERK, and P38 activators such as sulfuretin and chrysotoxine have shown efficacy in in vitro models of PD, by blocking apoptosis. Pariyar et al showed that sulfuretin protects neuronal cells against MPP + -induced damage through the activation of ERK and its downstream anti-apoptosis effector, Bcl-2, in SH-SY5Y cells [54]; however, sulfuretin has not been studied in an in vivo PD model. In addition, sulfuretin protected dopaminergic neurons from amyloid beta neurotoxicity in an in vitro model of Alzheimer’s disease [55].…”
Section: Discussionmentioning
confidence: 99%
“…Sulfuretin reduced caspase-3 and PARP activity accompanied by a reduction of intracellular reactive oxygen species (ROS) production and recovered the normal mitochondrial membrane potential. The mechanism involved the augmentation of the phosphorylation of Akt, GSK-3β and Erk pathway, confirmed by the disappearance of the cytoprotective effects of sulfuretin following the administration of PI3K/Akt and Erk inhibitors ( 78 ). Vitexin, a glucoside derivative of apigenin and several other flavonoids had similar protective effects on cell and mouse models of PD ( 79 ).…”
Section: Neurological Diseasesmentioning
confidence: 92%
“…This compound was also isolated from the heartwood of D. odorifera [11]. Sulfuretin possesses antiinflammatory [23], anti-cancer [24] and neuroprotective activities [25].…”
Section: Resultsmentioning
confidence: 99%